An Overview of Semi Trailer Articulated Vehicle Suspension and Control - Sunday Bako; Muhammed Bello Umar; Nuhu Mba Gora; Yusuf Saad; Paul Oscar Yahaya (Western European Studies, 2023)
This paper presents an overview of semi trailer articulated vehicle suspension and control. These vehicles are the common means of transporting industrial products. However, traffic clashes on these vehicles are destructive, and have leads to loss of lives and properties. Therefore, this paper aimed to review some literatures on this subject area in order to improve the vehicle safety and stability. It was noted that suspension system design is one of the main factors affecting tire wear. While, larger unsprung mass in rigid axles or dependent suspension systems compared to those on independent suspension systems influences the road tire contact, and consequently the driving dynamics in a negative way. Therefore, these problems can be minimized by keeping the unsprung mass as low as possible. It was noted that the Rearward Amplification Ratio (RWA) is an important parameter for determining the rollover propensity of this vehicle, because it can be involved in jack-knifing if the fifth wheel is positioned too far from the rearward position. However, more research works are needed on energy harvesting of semi trailer articulated vehicle suspension system
Keywords: Brake and Suspension Control; Rear Axle Positioning